A comparison of ground vehicle mobility analysis based on soil moisture time series datasets from WindSat, LIS, and in situ sensors. (June 2016) - Stevens, Maria T.; McKinley, George B.; Vahedifard, Farshid
Highlights: Soil moisture is a key terrain variable in ground vehicle off-road mobility. Mobility of six vehicles was examined in three test sites. Results from soil moisture sources of WindSat, LIS, and in situ sensors were compared. Soil moisture errors were found to produce significant errors in mobility analysis. Abstract: Soil moisture is a key terrain variable in ground vehicle off-road mobility. Historically, models of the land water balance have been used to estimate soil moisture. Recently, satellites have provided another source of soil moisture estimates that can be used to estimate soil-limited vehicle mobility. In this study, we compared the off-road vehicle mobility estimates based on three soil moisture sources: WindSat (a satellite source), LIS (a computer model source), and in situ ground sensors (to represent ground truth). Mobility of six vehicles, each with different ranges of sensitivity to soil moisture, was examined in three test sites. The results demonstrated that the effect of the soil moisture error on mobility predictions is complex and may produce very significant errors in off-road mobility analysis for certain combinations of vehicles, seasons, and climates. This is because soil moisture biases vary in both direction and magnitude with season and location. Furthermore, vehicles are sensitive to different ranges of soil moistures. Modeled vehicle speeds in the dry time periods were limited by the interaction between soil traction and the vehicles' powertrain characteristics. In the wet season, differences in soil strength resulted in more significant differences in mobility predictions.